The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.02.21.481268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of PNA-based antisense antibiotics targeting various essential genes in uropathogenic Escherichia coli

Abstract: Antisense peptide nucleic acids (PNAs) that target mRNAs of essential bacterial genes exhibit specific bactericidal effects in several microbial species, but our mechanistic understanding of PNA activity and their target gene spectrum is limited. Here, we present a systematic analysis of PNAs targeting eleven essential genes with varying expression levels in uropathogenic Escherichia coli (UPEC). We demonstrate that UPEC is susceptible to killing by peptide-conjugated PNAs, especially when targeting the widely… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 118 publications
(257 reference statements)
2
9
0
Order By: Relevance
“…To exploit the cell-free, low-volume nature of INRI-seq, we globally analyzed the influence of an antisense PNA on translation. In line with in vivo data 27, 28 , we found that acpP -PNA is specific for its target, acpP . Downregulation of PNA off-targets that harbor mismatches in the complementary sequence requires substantially higher PNA concentrations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To exploit the cell-free, low-volume nature of INRI-seq, we globally analyzed the influence of an antisense PNA on translation. In line with in vivo data 27, 28 , we found that acpP -PNA is specific for its target, acpP . Downregulation of PNA off-targets that harbor mismatches in the complementary sequence requires substantially higher PNA concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Gratifyingly, a recent study investigating the effects of acpP -PNA on global transcript levels in a uropathogenic E. coli (UPEC) strain observed very similar off-target effects. Of the four off-targets identified by INRI-seq, gpmM and ugpQ were among the top regulated transcripts upon addition of acpP -PNA 27 . These findings should aid future PNA design by providing a framework to weigh the predicted specificity of PNAs according to their predicted off-targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports using different E. coli strains showed that PNA-mRNA melting temperature (T m ) positively correlates with growth inhibition (Goltermann et al 2019) and is associated with in vitro translation inhibition of the target gene (Popella et al 2022). We therefore integrated T m predictions for PNA-RNA duplexes as a feature in MASON (see methods).…”
Section: Resultsmentioning
confidence: 99%
“…To test whether these results are specific to Salmonella , we applied the same bioinformatics analysis to a published transcriptomic data set in which UPEC were treated with 11 different PNAs targeting various essential genes (Popella et al 2022). The overall transcriptomic pattern closely resembles the data in the present study (Figure 3A, B).…”
Section: Resultsmentioning
confidence: 99%